Implementation of the Rational Unified Process (Rup) Method in Designing a Web-Based Certification Scheduling Application (Citation) on Itcc Itpln - Hendra Jatnika; Mochamad Farid Rifai; Lydia Tiomas Evalien Napitupulu (Syntax Idea)
This research discusses the Certification Scheduling application (SITASI) / processing website that can manage data and schedule certification activities which aim to assist ITCC assistants and laboratory heads in carrying out certification activities. Difficulties in data management are known to still run sequentially using different software, thus causing inefficiency in time utilization. In the design of this application, the author uses the RATIONAL UNIFIED PROCESS (RUP) method which ensures practically using the Unified Modeling Language (UML) or object-oriented. Based on the implementation of the method in the design of the SItasi application, it has been proven that the application can assist ITCC in managing data and scheduling certification to be integrated so that the creation of an integrated application door that is used for effective use of time is fulfilled.